Burzyński yield condition vis-à-vis the related studies reported in the literature - PĘCHERSKI, R. B. (Engineering Transactions, 2014)
The paper is written in accompaniment of the publication of English translation of W. Burzyński’s paper, which deals with the yield criterion for materials revealing the sensitivity of yield strength to pressure derived by W. Burzyński during preparation of his doctor thesis in 1927. More recently the dependence of yield strength on pressure is related to the so-called strength differential (SD) effect, i.e. asymmetry of elastic range, cf. e.g. Therefore, the original Burzyński’s formulation of yield condition remains actual and acquires increasing significance. The position of Burzyński’s energy-based approach in the literature is reported and his main achievement in this field concerning the recent studies is discussed.